Effects of wind mass-loss on the observational properties of Type Ib and Ic supernova progenitors. Issue Volume 16:Issue S366(2020) (November 2020) - Yoon, Sung-Chul; Jung, Moo-Keon; Jin, Harim; Kim, Hyun-Jeong
Abstract: Progenitors of Type Ib and Ic supernovae (SNe) are stripped envelope stars and provide important clues on the mass-loss history of massive stars. Direct observations of the progenitors before the supernova explosion would provide strong constraints on the exact nature of SN Ib/Ic progenitors. Given that stripped envelope massive stars can have an optically thick wind as in the case of Wolf-Rayet stars, the influence of the wind on the observational properties needs to be properly considered to correctly infer progenitor properties from pre-SN observations. Non-LTE stellar atmosphere models indicate that the optical brightness could be greatly enhanced with an optically thick wind because of lifting-up of the photosphere from the stellar surface to the wind matter, and line and free-free emissions. So far, only a limited number of SN Ib/Ic progenitor candidates have been reported, including iPTF13bvn, SN 2017ein and SN 2019yvr. We argue that these three candidates are a biased sample, being unusually bright in the optical compared to what is expected from typical SN Ib/Ic progenitors, and that mass-loss enhancement during the final evolutionary stage can explain their optical properties.